Implementation of SPADA UWGM in Online Learning - Gamar Al Haddar (AL-ISHLAH: Jurnal Pendidikan, 2021)
This research was motivated by the obligation to conduct online lectures in the odd semester of 2020-2021 during the Covid-19 Pandemic. To prevent the transmission of the Covid-19 virus, associ ations involving large numbers of people are unallowed. Therefore, Widya Gama Mahakam University provides a SPADA application accessible by lecturers and students for a more convenient lecture. This study aimed to analyze the use of online applications in online learning. This research was qualitative. The data collection techniques used were interviews and documentation. Testing the validity of the data was carried out by triangulating the source. Based on the research results, at the planning stage, the SPADA UWGM application has provided a complete system for lecturers to make conceptual and systematic planning. At the implementation stage, the SPADA UWGM application helps lecturers to distribute recovery materials, conduct interactive discussions through forums. However, for face-to-face online, there are still obstacles, especially in networks difficult to stabilize. Hence, learning through online classrooms and conferences is less effective using this application. The SPADA UWGM application interestingly contributes to the evaluation stage, especially to easily fill questions through question banks, assessments, and feedback from lecturers to students.